(untitled) (ABUJA JOURNAL OF BUSINESS AND MANAGEMENT, 2024)
The success of any educational organization depends heavily on the effectiveness of its academic staff, who are tasked with transferring knowledge, and supervising students. The study examined job satisfaction and performance of academic staff in Federal University Lokoja, Kogi State. The study delves with problems which include among others unpaid earned academic allowance, organizational politics, and inadequate research funding. The study used survey research design. The population of the study was 473 Academic staff of Federal University Lokoja Kogi state, with a sample size of 216. Simple random sampling technique was used for selecting respondent. Data were collected from primary sources via structured questionnaire. Data were analyzed using Descriptive statistics, Ordinary Least Square (OLS) linear regression technique was used to test the hypothesis through E-view statistical software package version 23. The finding of the study revealed that there is a positive significant relationship between job satisfaction (earned academic allowance, organizational politics and research funding) on teaching and learning (TL) in Federal University, Lokoja, Kogi. Hypotheses two indicate a positive significant relationship between job satisfaction (earned academic allowance, organizational politics and research funding) on research and publications (RAP) of academic Staff in Federal University, Lokoja, Kogi State. Hypotheses three further revealed a positive significant relationship between job satisfaction (earned academic allowance, organizational politics and research funding) and community service (CMS) in Federal University, Lokoja, Kogi State. The study concludes that there is positive significant relationship of job satisfaction (earned academic allowance, organizational politics and research funding) on teaching and learning, research and publications, and on community service in Federal University Lokoja, Kogi State. The study recommends that: the Federal Government should mainstream earned academic allowance as part of the monthly salaries of academic staff in order to enhance the quality of teaching and learning in Federal University Lokoja, Kogi State and to prevent recurring industrial disputes; the management of Federal University Lokoja, Kogi State, should continuously engage TETFUND and other funding agencies to increase the staffs’ access to research funds thereby encouraging research and publications; The management of Federal University Lokoja, Kogi State should avoid unhealthy politics in order to enhance the contribution of academic staff to community service.